PENGELOLAAN HUTAN KOTA BERKELANJUTAN: TINJAUAN ASPEK TEKNIS, ALAM DAN SOSIAL (Studi di Hutan Kota Srengseng dan Hutan Kota Universitas Indonesia) - D. K. Sukarta (Bumi Lestari Journal of Environment, 2013)
AbstractThis study was conducted at Srengseng Urban Forest and Universitas Indonesia UrbanForest, to indentify the structure of the urban forest, its effectiveness in lowering citytemperatures, and to predict the people behavior towards urban forest using the thoery ofplanned behavior. The approach which is used in this study is aquantitative approach andis also supported by qualitative data. The method which is used is observasional fieldstudy and data collected by closed questionnaires and interview techniques. Our studyobserves a total of 24sample plots, consisting of 4 plots examples in SrengsengUrban Forestand 20 sample plotsin Universitas Indonesia Urban Forest. The number of respondents intotal90 people, comprised of 47 respondents in Srengseng Urban Forest and 43 respondentsin Universitas Indonesia Urban Forest. Vegetation analysis implementedby observing thecondition of the stands includes plant species,diameter, and height of plants ranging fromseedling stotrees. It’s continued by an analysis of the diversity, distribution, and dominanceof vegetation using theShannon diversity index, dominance index, and the important valueindex. The results of the vegetation analysis shows that Universitas Indonesia UrbanForest has a higher diversity of vegetation t han in Srengseng Urban Forest. The relationshipbetween the technical aspects which is density and the natural aspects which are thetemperature showed that temperature is related to density. The analysis of the socialaspects describe that respondents have a good perception of the urban forest although thebehavior seems inconsistent withhis perception. Statistical test results showed that thebehavior of the respondents are influenced by subjective norms that existin their community.